Penerapan Metode Mubassarah dalam Pengajaran Bahasa Arab di Kelas 10 MA Nahdlatus Shaufiah Wanasaba - Zakaki, Zakaki (Lembaga Yasin AlSys, 2022)
The mubasyarah method is a method that teaches that teaching foreign languages ​​is not the same as teaching the exact sciences. If in teaching exact sciences, students are required to be able to memorize certain formulas, but in this mubasyarah method students are trained to practice directly saying certain words or sentences even though the sentences are still foreign and not understood by children. These are, observation, interviews and documentation. Interviews were conducted with students and Arabic teachers of class 10 MA Nahdlatus Shaufiah Wanasaba, while documentation was conducted to request supporting documents for research purposes such as lesson plans, school data, and so on. Based on the results of observations made by researchers in grade 10 MA Nahdlatus Shaufiah Wanasaba, it can be seen that learning Arabic using the mubasyarah method begins with preliminary activities, core activities and closing activities. The method taught is guided by the procedure for applying the mubasyarah method.